2017
DOI: 10.1108/jabs-08-2015-0129
|View full text |Cite
|
Sign up to set email alerts
|

Online retailers connecting to the youth segment through Facebook (A study on the influence of gender and personality type)

Abstract: Purpose The purpose of this paper is to develop an understanding of the different personality types and Facebook behavior of the young Indian consumers in the context of e-tailing. With the increased popularity of Facebook, consumers and e-tailers are using it as a platform to connect better with each other. This paper makes an attempt to study the motive and online purchasing behavior of youth by examining Facebook posts and understanding their relationship with personality and gender. Design/methodology/app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 65 publications
(79 reference statements)
1
5
0
Order By: Relevance
“…Facebook, Twitter etc.) to increase visibility and address consumers concerns would accelerate adoption curve, especially among tech-savvy consumers like youth (Mishra and Ayatham, 2017; Khandelwal et al , 2018) besides lessening their price sensitivity. They can also strengthen the positive attitude towards buying by the increasing availability of relevant food products and explore the utility of new technology like Blockchain (Cuervo-Cazurra et al , 2020 ) to increase traceability, transparency and consumer trust.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…Facebook, Twitter etc.) to increase visibility and address consumers concerns would accelerate adoption curve, especially among tech-savvy consumers like youth (Mishra and Ayatham, 2017; Khandelwal et al , 2018) besides lessening their price sensitivity. They can also strengthen the positive attitude towards buying by the increasing availability of relevant food products and explore the utility of new technology like Blockchain (Cuervo-Cazurra et al , 2020 ) to increase traceability, transparency and consumer trust.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…Reflecting previous offline studies linking traits with motives for offline media use (such as Finn, 1997 ; Krcmar and Kean, 2005 ), Hollenbaugh and Ferris (2014) then sought to understand people’s motives for using social media. Among the relationships identified in research to date, extraversion has been linked with the motive to connect with new friends ( Bhattacharya et al, 2014 ; Orchard et al, 2014 ) and existing peers ( Bhattacharya et al, 2014 ), and to share information about themselves ( Mishra and Ayatham, 2017 ). Krishnan and Atkin (2014) also demonstrated that, for those high in extraversion, infotainment was likely to be a motive for using social networks.…”
Section: Introductionmentioning
confidence: 99%
“…Neuroticism also relates to social media use as a means of escapism ( Orchard et al, 2014 ) or as a means of coping with pressure ( Marino et al, 2016 ), with social media satisfying a desire for acceptance and inclusion ( Marshall et al, 2015 ). Openness has been related to use of social media to connect with like-minded people and find new friends ( Bhattacharya et al, 2014 ), use social networking sites for learning ( Chou and Chiu (2015) and sharing information Marshall et al, 2015 ), and to search for products ( Bhattacharya et al, 2014 ; Mishra and Ayatham, 2017 ). Those high in agreeableness are also likely to use social media to maintain relationships ( Horzum, 2016 ) and to use Pinterest specifically to entertain and inform themselves ( Lin et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the findings of the current study indicate that social media use in Saudi Arabia has a direct negative effect on psychological well-being and that may make specialists and creators of content on social media platforms take into consideration this result when they design applications for the public. Mishra and Ayatham (2017) state that analyzing and standing on the relationships that arose from using social media influence planners of strategies related to social media and the impact of these relations would increase when it comes to using social media for business.…”
Section: Implication For Practicementioning
confidence: 99%